2020
DOI: 10.1007/s00421-020-04467-6
|View full text |Cite
|
Sign up to set email alerts
|

PGC-1α alternative promoter (Exon 1b) controls augmentation of total PGC-1α gene expression in response to cold water immersion and low glycogen availability

Abstract: This investigation sought to determine whether post-exercise cold water immersion and low glycogen availability, separately and in combination, would preferentially activate either the Exon 1a or Exon 1b Peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α) promoter. Through a reanalysis of sample design, we identified that the systemic cold-induced augmentation of total PGC-1α gene expression observed previously (Allan et al. in J Appl Physiol 123(2):451–459, 2017) was largely a result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…We propose that these novel discrete RNA signals represent brain-specific lncRNAs that may originate at brain-associated exon B1 but may not extend into the canonical part of the PPARGC1A gene and so were not previously detected. These findings, the unexpected use of the distal and Liver promoters supplementing the Prox and Alt promoters of PPARGC1A in SkM, and the preferential use of the distal promoter in ESC need follow-up investigation given the importance of PPARGC1A transcription levels and isoform usage to exercise, aging, SkM hypertrophy, and disease, including facioscapulohumeral muscular dystrophy, Alzheimer’s disease, amyotrophic lateral sclerosis, Huntington’s disease, and ischemia [ 50 , 51 , 63 , 83 , 84 , 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…We propose that these novel discrete RNA signals represent brain-specific lncRNAs that may originate at brain-associated exon B1 but may not extend into the canonical part of the PPARGC1A gene and so were not previously detected. These findings, the unexpected use of the distal and Liver promoters supplementing the Prox and Alt promoters of PPARGC1A in SkM, and the preferential use of the distal promoter in ESC need follow-up investigation given the importance of PPARGC1A transcription levels and isoform usage to exercise, aging, SkM hypertrophy, and disease, including facioscapulohumeral muscular dystrophy, Alzheimer’s disease, amyotrophic lateral sclerosis, Huntington’s disease, and ischemia [ 50 , 51 , 63 , 83 , 84 , 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst CWI was not conceived as a strategy specifically meant to supplement exercise adaptations, there was substantial interest in examining how recovery-based CWI might influence skeletal muscle adaptations to endurance exercise (Ihsan et al, 2014b(Ihsan et al, , 2015(Ihsan et al, , 2020bAllan et al, , 2019Allan et al, , 2020. This line of enquiry is likely motivated by work in cell cultures and rodents demonstrating robust increases in mitochondrial markers following exercise and cold exposure with common mechanisms involving PGC-1α.…”
Section: Endurance Exercise Adaptation To Post-exercise Cwi: Discrepa...mentioning
confidence: 99%
“…Yet, the first study to address this extends considerably back to 2006 . Following a hiatus, a series of studies examining the influence of CWI on adaptation to endurance exercise emerged from independent laboratories (Ihsan et al, 2014b(Ihsan et al, , 2015(Ihsan et al, , 2020bAllan et al, , 2019Allan et al, , 2020, which was followed up by others examining the influence of CWI on resistance training adaptations . A recent metaanalytical review showed that CWI effects on exercise adaptations are mode-dependant, where resistance training adaptations were diminished, whilst aerobic exercise performance seemed unaffected .…”
Section: Introductionmentioning
confidence: 99%
“…Whilst CWI was not conceived as a strategy specifically meant to supplement exercise adaptations, there was substantial interest in examining how recovery-based CWI might influence skeletal muscle adaptations to endurance exercise (Ihsan et al, 2014b(Ihsan et al, , 2015(Ihsan et al, , 2020bAguiar et al, 2016;Joo et al, 2016;Allan et al, , 2019Allan et al, , 2020Broatch et al, 2017). This line of enquiry is likely motivated by work in cell cultures and rodents demonstrating robust increases in mitochondrial markers following exercise and cold exposure with common mechanisms involving PGC-1α.…”
Section: Endurance Exercise Adaptation To Post-exercise Cwi: Discrepancy Between Molecular Signaling and Exercise Performancementioning
confidence: 99%
“…Yet, the first study to address this extends considerably back to 2006 (Yamane et al, 2006). Following a hiatus, a series of studies examining the influence of CWI on adaptation to endurance exercise emerged from independent laboratories (Ihsan et al, 2014b(Ihsan et al, , 2015(Ihsan et al, , 2020bAguiar et al, 2016;Joo et al, 2016;Allan et al, , 2019Allan et al, , 2020Broatch et al, 2017), which was followed up by others examining the influence of CWI on resistance training adaptations (Frohlich et al, 2014;Roberts et al, 2015;Figueiredo et al, 2016;D'Souza et al, 2018;Fyfe et al, 2019;Fuchs et al, 2020;Peake et al, 2020;Poppendieck et al, 2020). A recent metaanalytical review showed that CWI effects on exercise adaptations are mode-dependant, where resistance training adaptations were diminished, whilst aerobic exercise performance seemed unaffected (Malta et al, 2021).…”
Section: Introductionmentioning
confidence: 99%